Gender (s) and education: Approaches to the Latin American and the Caribbean context - Trimiño Velásquez, Celina De Jesús (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
The women, through their struggles and the bearings of the feminisms have achieved the right to access to higher education in almost all western countries, which is a great achievement. This massive influx has not substantially changed the gender relations into these institutions, or in other areas of contemporary society. The aim of this article is to do a critical review in order to provide some elements for the analysis in the Latin America and the Caribbean context from a feminist perspective. It examines publications and research on feminist theories, the emergence of feminisms and women’s education. In the reflection, it shows that the feminist theories have disputed the patriarchal postulates that legitimize the masculine dominance in the public and private. It allows unveiling the andro-centric bias in the sciences, and presenting arguments to develop proposals that take into account situations and experiences of the diversity of women, in order to outline their contributions and their participation in social changes. The feminist theories and actions become relevant in this process; it showed the influence of women´s movements. Education is also key and it must commit to change the patriarchal culture, for that reason it is relevant to create the conditions for a comprehensive education that equates feminine and masculine gaze about building a more just world.